Revision of Notoglanidium and related genera (Siluriformes: Claroteidae) based on morphology and osteology - Geerinckx, Tom; Vreven, Emmanuel; Dierick, Manuel; Hoorebeke, Luc Van; Adriaens, Dominique (Zootaxa, 2013)
Apart from the well-demarcated genera Auchenoglanis and Parauchenoglanis, Auchenoglanidinae, one of the two subfamilies of the African catfish family Claroteidae, suffers from poor resolution at the generic level. For the remaining genera, Notoglanidium, Liauchenoglanis, Platyglanis and Anaspidoglanis, generic discriminations are rudimentary. In addition, several included species are poorly defined and barely represented in scientific collections. Until now, no study has included morphological data for all currently known species, and for many species osteological data were non-existent. Molecular data for most species are lacking as well. Here, a comprehensive account of the morphology and osteology is given of all species included in these four genera. Using computed tomography (CT scanning) as well as clearing and staining, osteological characters were combined with biometric, meristic and other morphological data to revise the status of these genera and included species. Morphological and osteological data, submitted to a phylogenetic analysis, agree with metric and meristic data that all Liauchenoglanis, Platyglanis and Anaspidoglanis cannot be discerned from Notoglanidium; their genus and type species descriptions fail to be distinguished from Notoglanidium. Here their synonymy is proposed, resulting in a single valid genus, including nine species of which the validity is confirmed. A key to the genus and included species, as well as a diagnosis and description for each of them, are provided.